Implementasi Akuntansi Qardhul Hasan Dalam Penyajian Laporan Keuangan (Analisis Pembiayaan Qardhul Hasan Di Unit Simpan Pinjam Pola Syariah Banyuwangi) - Syarofi, Muhammad (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2021)
Non-bank financial institutions, sharia cooperatives are formed to provide welfare to their members, by realizing sharia principles, avoiding usury to gain worldly benefits and getting falah in the hereafter. One of the applications is in the transaction of virtue of the qardhul hasan contract funds given to members or micro-enterprises that are deemed to need them. The qardhul hasan contract is considered to be in great demand by members of sharia cooperatives because it has social functions such as CSR (corporate social responsibility) contained in banking financial institutions. The implementation of the presentation of the financial statements of the qardhul hasan virtue fund by the Islamic cooperative institution USPPS Ausath is able to be applied in an accountable, transparent and effective manner in the accounting records of financial statements.This is evidenced by the details between the loan principal amount, loan principal installments and monthly wages, an interesting thing is in the calculation of wages, where USPPS Ausath applies monthly wages according to the principal loan amount received by members The ujrah can be paid in installments and repaid according to the length of the loan, without having to pay all the total annual wages. Keywords: Akuntansi Qardhul Hasan dan Penyajian Laporan Keuangan